Tindak Tutur Ekspresif dalam Podcast Raditya Dika “Cerita Ruang IGD” - Nur Syavika; Wiji Rahayu; Fatmawati F (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the forms and functions of expressive speech acts found in Raditya Dika’s podcast entitled Cerita Ruang IGD. The research employs a qualitative approach using a content analysis method. Data were collected through listening and note-taking techniques applied to the utterances in the podcast. Expressive speech acts are utterances that reflect the speaker’s psychological state toward a particular situation, such as expressing gratitude, giving compliments, stating beliefs, and expressing disappointment. The results show that there are five instances of expressions of gratitude, two instances of expressions of belief, five instances of compliments, and one instance of disappointment. Each type of expressive speech act has social and emotional functions in building interpersonal relationships, as well as in portraying the speaker’s character and self-image. In this context, Raditya Dika and dr. Gia Pratama use expressive speech acts not only as a means of communication but also to strengthen emotional impressions and create a warm and intimate conversational atmosphere. This study contributes to pragmatic studies, particularly in understanding the contextual use of language in everyday communication through digital media. The findings highlight the importance of language awareness in social and emotional contexts and serve as a reference for further research in language analysis in online media.